Hubungan Antara Penggunaan Media Pembelajaran dengan Aktivitas Belajar pada Tematik Terpadu - Wahyu Neza Eka Formi; Mai Sri Lena (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research aims to know a relationship between the use of instructional media on learning activities in integrated thematic learning in class V of primary school,KamangMagek District. The type of this research is quantitativeresearch by using the correlational method. Sampling technique using population sampling techniques. The sample of this researchis amounted to 72 students of class V of primary School Cluster II KamangMagek District.Based on the data analysis that has been done, the result of this research shows that there is a significant relationship between the use of instructional media on learning activities in integrated thematic learning in class V of primary School Cluster II KamangMagek District. This is evidenced by the value of rcount = 0.688>rtable = 0.235 and significance value of 0.000 <0.005 which means that Ho is rejected and Ha is accepted, so the hypothesis which says "there is a relationship between the use of learning media with learning activities in integrated thematic learning in class V SD NegeriGugus Group II KamangMagek District " is accepted.